2023
DOI: 10.1186/s12913-023-09811-y
|View full text |Cite
|
Sign up to set email alerts
|

Linking leadership development programs for physicians with organization-level outcomes: a realist review

Abstract: Background Hospitals invest in Leadership Development Programs (LDPs) for physicians, assuming they benefit the organization’s performance. Researchers have listed the advantages of LDPs, but knowledge of how and why organization-level outcomes are achieved is missing. Objective To investigate how, why and under which circumstances LDPs for physicians can impact organization-level outcomes. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…However, the literature review also showed that while CL is learnable, few clinicians have the conceptual or practical skills for continuous improvement of services [11]. Vast amounts of CL-PD are offered to address this need, but in the literature, there is a paucity of high-quality evidence of CL-PD's effectiveness on healthcare sustainability [56,[59][60][61], which is in itself not educationally or financially sustainable [53,57]. A deeper gap was found to underlie this challenge: despite CL being widely identified as a central factor for sustainable healthcare, there is no consensus understanding of how CL is learned [54] and a discussion of CL-education/training has only recently emerged in the sustainability literature [34], with a call for more research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the literature review also showed that while CL is learnable, few clinicians have the conceptual or practical skills for continuous improvement of services [11]. Vast amounts of CL-PD are offered to address this need, but in the literature, there is a paucity of high-quality evidence of CL-PD's effectiveness on healthcare sustainability [56,[59][60][61], which is in itself not educationally or financially sustainable [53,57]. A deeper gap was found to underlie this challenge: despite CL being widely identified as a central factor for sustainable healthcare, there is no consensus understanding of how CL is learned [54] and a discussion of CL-education/training has only recently emerged in the sustainability literature [34], with a call for more research.…”
Section: Discussionmentioning
confidence: 99%
“…This study addresses this gap in the literature through a novel approach, informed by theoretical literature on professional learning of sustained innovation and continuous improvement. Acknowledging the challenges in identifying causal pathways from PD-courses to organisational effects on sustainability, and a lack of extant conceptual and methodological tools of evaluation [7,57,59,60], we proposed that a constitutive step of theorising and empirically analysing how leadership is learned during CL-PD is needed first. While many evaluations focus on and compare the content and features of CL-PD interventions, evidence has suggested that learning processes during CL-PD are more important [61,[63][64][65][76][77][78].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation